Conservation of architectural heritage : a culmination of selected research papers from the Second International Conference on Conservation of Architectural Heritage (CAH-2), Egypt 2018 /: a culmination of selected research papers from the Second International Conference on Conservation of Architectural Heritage (CAH-2), Egypt 2018. ([2019]) - Unknown
No abstract available